أثر الرشاقة الاستراتيجية في تحقيق التميز التنظيمي : دراسة حالة لعينة من وكالات السياحة والأسفار بولايات الوادي – بسكرة – ورقلة – تبسة – باتنة - ستو فاطمة الزهرة (University Eloued جامعة الوادي, 2024)
الملخص: هدفت هذه الدراسة إلى التعرف على أثر الرشاقة الاستراتيجية بأبعادها في تحقيق التميز التنظيمي بوكالات السياحة والأسفار، ولتحقيق أهداف الدراسة تم الاعتماد على المنهج الوصفي التحليلي والاستبيان كأداة لجمع البيانات والاختبارات الإحصائية المناسبة لاختبار فرضيات الدراسة والإجابة على تساؤلاتها، وحصر مجتمع الدراسة في الإطارات المسيرة بوكالات السياحة والأسفار بكل من ولاية (الوادي، بسكرة، ورقلة، تبسة وباتنة)، وقد تم اعتماد أسلوب العينة العشوائية البسيطة التي قدرت بـــــ 400 مفردة. وقد أظهرت نتائج الدراسة أن مستوى ممارسة الرشاقة الاستراتيجية بوكالات السياحة والأسفار محل الدراسة قد جاء مرتفعا لكل الأبعاد ما عدا بعد وضوح الرؤية الذي جاء بمستوى متوسط، أما مستوى التميز التنظيمي فقد جاء مرتفعا بجميع أبعاده، كما أظهرت نتائج الدراسة وجود علاقة طردية قوية بين كل من الرشاقة الاستراتيجية والتميز التنظيمي، وأن هناك أثرا لأبعاد الرشاقة الاستراتيجية في تحقيق التميز التنظيمي، كما توصلت الدراسة إلى عدم وجود فروق لمتوسطات إجابات أفراد عينة الدراسة تعزى لكل من (الجنس، السن والمسمى الوظيفي) حول كل من متغيري الدراسة إضافة إلى عدم وجود فروق تعزى لـــ (الخبرة) بالنسبة لمتغير التميز التنظيمي، في حين أن هناك فروقا لمتوسطات إجابات أفراد عينة الدراسة تعزى لمتغير (المستوى التعليمي) لكل من متغيري الدراسة إضافة إلى وجود فروق تعزى لـــ (الخبرة) بالنسبة لمتغير الرشاقة الاستراتيجية. وقد خلصت الدراسة إلى مجموعة من التوصيات تمثلت أبرزها في ضرورة إعطاء أهمية لمفهوم الرشاقة الاستراتيجية من قبل وكالات السياحة والأسفار محل الدراسة، وذلك باعتماده ونشر فلسفته وتبني مبادئه كأسلوب من أساليب التأقلم والتعايش وتعزيز ممارسته في جميع المستويات باعتباره عاملا جوهريا وله أهمية كبيرة في تعزيز التميز التنظيمي. This study aimed to identify the impact of strategic agility with its dimensions on achieving organizational excellence in tourism and travel agencies. To achieve the objectives of the study, the analytical descriptive approach was adopted and the questionnaire was used as a tool for data collection. Besides, the appropriate statistical tests were used to test the hypotheses of the study and answer its questions. The study population was limited to managers of tourism and travel agencies in each of the states (El-Oued, Biskra, Ouargla, Tebessa and Batna), and the simple random sample method which was estimated at 400 individuals was adopted. The findings of the study showed that the level of practice of strategic agility in the tourism and travel agencies studied was high for all the dimensions except for clarity of vision dimension which was at a medium level. However, the level of organizational excellence was high in all its dimensions. The results of the study also showed that there is a strong direct relationship between both strategic agility and organizational excellence, and that there is an impact of the dimensions of strategic agility in achieving organizational excellence. Moreover, the study found that there are no differences in the averages of the responses of the study sample members attributed to (gender, year, job title) about each of the two study variables as well as no differences attributable to (experience) for the organizational excellence variable. However, there are differences in the averages of responses of the study sample members attributable to (educational level) for both study variables in addition to differences attributable to (experience) for the strategic agility variable. The study concluded with a set of recommendations, the most prominent of which was the need to give importance to the concept of strategic agility by the studied tourism and travel agencies through adopting it, spreading its philosophy and adopting its principles as a method of adaptation and coexistence as well as promoting its practice at all levels as an essential factor of great importance in promoting organizational excellence.
أطروحة دكتوراه
Keywords: رشاقة استراتيجية; تميز تنظيمي; أهداف استراتيجية; وضوح الرؤية; وكالة سياحة وسفر; Organizational Excellence; Strategic Agility; Strategic Objectives; clarity of vision; Travel and Tourism Agency.